Geologic context and potential EVA targets at the lunar south pole. Issue 6 (15th September 2020) - Gawronska, A.J.; Barrett, N.; Boazman, S.J.; Gilmour, C.M.; Halim, S.H.; Harish,; McCanaan, K.; Satyakumar, A.V.; Shah, J.; Meyer, H.M.; Kring, D.A.
Highlights: Many geologic features of interest could be sampled during EVA near the lunar south pole. Optimal scientific sampling would be enhanced by a lunar rover due to variable topography. A layered terrain is exposed in part of the wall of Shackleton crater. Abstract: The lunar south pole is being targeted for exploration, in part, because it contains topographical high points with >50% illumination needed for solar power. Additionally, the south pole is being targeted because it contains permanently shadowed regions (PSRs), which may sequester resources in the form of volatile materials. Geologically, the pole lies on the rim of ~21 km diameter Shackleton crater, which is located on the topographic rim of the ~2, 500 km diameter South Pole-Aitken (SPA) basin, the largest and oldest basin on the Moon. To prepare for future missions, we conducted a photogeologic analysis of the walls, rim, and ejecta of Shackleton crater. Two types of underlying (target) terrains were identified. The impact penetrated and exposed (1) purest anorthosite (PAN) representative of primitive crust and (2) a layered terrain that is likely a series of impact ejecta deposits that stratigraphically cover the crystalline crust. Crew performing extravehicular activities (EVAs) near the south pole may be able to sample PAN; impact melt from Shackleton, SPA, and other pre-Nectarian and Nectarian-age impacts; and polar regolith, including material from small PSRs that may contain volatile components. The topography in the south polar region is dramatic, often producing slopes in excess of 15°, creating mobility challenges for astronauts during EVAs.